1994
DOI: 10.1002/mrd.1080370310
|View full text |Cite
|
Sign up to set email alerts
|

Sperm nuclear chromatin transformations in somatic cell‐free extracts

Abstract: HeLa cell extracts induced decondensation of lysolecithin permeabilized Xenopus, pig, and human sperm chromatin; decondensation began almost immediately on incubation in the extract and was completed within 10-20 min. The average enlargements of human and pig sperm nuclei were 15-fold and 3-fold, respectively. The structural organization of pig and human sperm chromatin was significantly different. Decondensation was differentially inhibited by Mg++ and polyamines; inhibition was least for Xenopus and most for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Although protamines constitute the major protein fraction in human sperm, histones, both canonical and variant versions of the core histones, are also present (Gatewood et al, 1990). Linker histones do not appear to be required for sperm chromatin condensation (Gatewood et al, 1990; Banerjee and Hulten, 1994). A recent study revealed that nucleosomes retained in sperm chromatin exhibit specific localization with respect to developmentally important loci, and that differential methylation of histones and DNA occurs at these positions (Hammoud et al, 2009).…”
Section: Epigenetic Mechanisms During Preimplantation Developmentmentioning
confidence: 99%
“…Although protamines constitute the major protein fraction in human sperm, histones, both canonical and variant versions of the core histones, are also present (Gatewood et al, 1990). Linker histones do not appear to be required for sperm chromatin condensation (Gatewood et al, 1990; Banerjee and Hulten, 1994). A recent study revealed that nucleosomes retained in sperm chromatin exhibit specific localization with respect to developmentally important loci, and that differential methylation of histones and DNA occurs at these positions (Hammoud et al, 2009).…”
Section: Epigenetic Mechanisms During Preimplantation Developmentmentioning
confidence: 99%
“…By mediating the availability of specific DNA sequences to regulatory proteins, chromatin accessibility in the form of chromatin condensation or relaxation is thought to be a major regulator of transcription (Orphanides and Reinberg 2002). Current methods of studying chromatin architecture either measure the accessibility of the genome as a whole (Banerjee and Hulten 1994) or of a few sub-kilobase regions (Reid et al 2000), but no technique is currently available to easily and simultaneously measure the chromatin accessibility of the whole genome at kilobase resolution (Urnov 2003;Crawford et al 2004).…”
mentioning
confidence: 99%
“…This "Chromatin Array" allows us to overcome the limited resolution and throughput problems of previous methods (Banerjee and Hulten 1994;Reid et al 2000) by using the multiplex nature of microarray experiments while retaining the high resolution of low-throughput chromatin accessibility measurement techniques. Because this new type of microarray experiment has a novel output, we developed methods to interpret the chromatin state from the relationship of the condensed fraction's hybridization intensity as compared with the intensity of total genomic DNA.…”
mentioning
confidence: 99%
“…male pronucleus formation by (1) employing eggs from different animal species [35,39], (2) somatic cell nuclei transfer to mature eggs [3,36], (3) handling somatic cell-free eggs and embryo extract [2,22,24,31], (4) cell-free preparation of cytoplasm from activated eggs or anucleate fragments of parthenogenetic eggs [5,29], and (5) ooplasmic factors [7,28,38].…”
mentioning
confidence: 99%